2017
DOI: 10.1177/0333102417690488
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship between type 1 diabetes mellitus and migraine. Data from the Nord-Trøndelag Health Surveys 1995–1997 and 2006–2008

Abstract: Aims The aim of this cross-sectional population-based study was to investigate the associations between migraine and type 1 and type 2 diabetes mellitus (DM). Methods We used data from the second (1995-1997) and third survey (2006-2008) in the Nord-Trøndelag Health Study. Analyses were made for the 26,121 participants (30-97 years of age, median 58.3 years) with known headache and DM status in both surveys, and for the 39,584 participants in the third survey (20-97 years, median 54.1 years). The diagnosis of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
7
24
1
Order By: Relevance
“…There was no association between diabetes and headache or migraine, and the existing literature has not demonstrated consistent associations either [3, 21]. We found hypertension to be significantly associated with MH, consistent with multiple studies [3, 22, 23] including one based on self-report [24].…”
Section: Discussionsupporting
confidence: 87%
“…There was no association between diabetes and headache or migraine, and the existing literature has not demonstrated consistent associations either [3, 21]. We found hypertension to be significantly associated with MH, consistent with multiple studies [3, 22, 23] including one based on self-report [24].…”
Section: Discussionsupporting
confidence: 87%
“…7 Interestingly, recent large population-based studies have consistently reported an inverse relationship between migraine and both type 1 and type 2 diabetes. [21][22][23][24] These studies suggest that diabetes or treatment of diabetes may have a protective effect on migraine development. It has been speculated that reduced pain sensitivity due to diabetic neuropathy, 25 and thereby altered pain thresholds of the trigeminal nociceptive system, or reduced cerebrovascular reactivity, 26 by prevention of vasodilation-induced migraine, 27 may lower the risk of migraine attack initiation in diabetics.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, recent large population‐based studies have consistently reported an inverse relationship between migraine and both type 1 and type 2 diabetes . These studies suggest that diabetes or treatment of diabetes may have a protective effect on migraine development.…”
Section: Discussionmentioning
confidence: 98%
“…Yet, a different study on the prevalence of migraine in patients with type 2 diabetes failed to find a positive association 20 . Finally, although a recent cross--sectional population-based study also failed to identify an inverse relationship between type 2 diabetes and headache, an association between type 1 diabetes and both headache (OR = 0.55, 95% CI 0.34--0.88) and migraine (OR = 0.47, 95 % CI 0.26--0.96) was found 21 .…”
Section: With the World Healthmentioning
confidence: 80%
“…13 Dissociative fugue 300.14 Dissociative identity disorder 300. 21 Agoraphobia with panic disorder 300.09…”
Section: Fundingmentioning
confidence: 99%